Synthesis of Ni(II) porphyrazine peripherally octa-substituted with the 4-tert-butylbenzylthio moiety and electronic properties of the Al/Ni(II)Pz/p-Si Schottky barrier diode - Keskin, Bahadir; Denktaş, Cenk; Altındal, Ahmet; Avcıata, Ulvi; Gül, Ahmet (Elsevier BV, 2012)
Abstract Magnesium porphyrazinate substituted with eight 4- tert -butylphenylthio-groups on the peripheral positions has been synthesized by cyclotetramerization of 1,2-bis(4- tert -butylphenylthio)maleonitrile in the presence of magnesium butanolate. The metal-free derivative was obtained by its treatment with trifluoroacetic acid, and further reaction of this product with nickel(II) acetate led to the metal porphyrazinate (M = Ni). These new compounds have been characterized by elemental analysis, together with FT-IR, 1 H NMR and UV–Vis spectral data. The electronic properties of a spin coated film of NiPz have been studied by fabricating metal–insulator–semiconductor (MIS) capacitors. Current–voltage ( I – V ) and capacitance–voltage ( C – V ) measurements were carried out. It was observed that the Al/NiPz/p-Si structure exhibits rectifying behavior with a barrier height value of 0.89 eV and with an ideality factor value of 1.81. It was seen that this value of the obtained barrier height is remarkably higher than those given for metal/Si semiconductor contacts in the literature. The Lien, So and Nicolet method, combined with conventional forward I – V , was used to extract the series resistance value and it was found to be 26 kΩ. High frequency C – V measurements were used to determine the mobile oxide charge in the NiPz layer and this was found to be 1.6 × 10 11  cm −2 .